AN UPPER BOUND FOR THE COMPLEXITY OF LINEARIZED COVERINGS IN A FINITE FIELD - Nurijanyan, H. K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
The minimal number of systems of linear equations with n unknowns over a finite field $F_q$,  such that the union of all solutions of the systems forms an exact cover for a given subset in $F_q^n$, is the complexity of a linearized covering. An upper bound for the complexity for “almost all” subsets in $F_q^n$ is presented.
Keywords: finite fields; system of linear equations over finite fields; linearized coverings